Synergy of Islamic Religious Education and the SDGs : Integrating Character Education and Global Citizenship (International Forum of Researchers and Lecturers, 2025)
This article aims to examine the potential integration between Islamic Religious Education (PAI) and the principles of the Sustainable Development Goals (SDGs) in shaping character education and global citizenship awareness. By analyzing a range of scholarly works, this study highlights how Islamic values such as justice (‘adl), responsibility (mas’uliyyah), social care (ta‘āwun), and balance (mīzān) align closely with the core principles of the SDGs. Through a literature review and content analysis, the study provides evidence that Islamic values are essential in fostering individuals who are not only religiously devout but also critically aware of global issues. These individuals are better equipped to become agents of change within their communities and on the global stage. The study underscores the importance of integrating PAI as a strategic component for the moral and spiritual development of learners, promoting their engagement in both local and international efforts to achieve sustainable development. The findings of this article suggest that while PAI is well-positioned to contribute to the realization of SDGs, particularly in areas of justice, equity, and social welfare, a transformation in teaching approaches is necessary. Traditional methods of teaching PAI need to evolve to be more contextual, active, and integrative, encompassing a more global perspective in line with the SDGs. Furthermore, there needs to be greater synergy between educational institutions, curriculum policies, and teaching methods to maximize the role of PAI in shaping future generations who are not only religiously grounded but also socially responsible. This article concludes by recommending strengthening innovative teaching methods and fostering collaborations that enhance the capacity of PAI to support just and inclusive sustainable development. This approach will ensure that PAI contributes effectively to achieving the SDGs in the context of character education and global citizenship.